LyoScope: a portable lyoluminescence reader prototype - Biernacka, Magdalena; Maternicki, Krzysztof; Sądel, Michał; Kreutzer, Sebastian (Radiation measurements, 2025)
We present the design of LyoScope, a portable, compact device for measuring lyoluminescence (LL). Lyoluminescence is a phenomenon occurring during the dissolution of previously irradiated material. Measurements facilitate the estimation of the total dose absorbed by the material since its last exposure to light, heat, or moisture. Due to its versatility, LyoScope is suitable for both environmental and laboratory measurements. Its elementary design enables self-assembly, such as through 3D printing. We provide a detailed technical description and present first performance tests: the minimum detectable dose for NaCl was determined at ∼5 mGy, repeatability tests on natural halite achieved a variation of only ∼2.4 %, and fading experiments revealed that ∼35-40 % of the LL signal is lost within weeks, followed by stabilization of ∼35-60 % of the signal. In addition, we demonstrate the option of attaching an EM-CCD camera to our setup enabling spatially-resolved LL measurements and a visualization of the dissolution process. Our results underscore that LyoScope enables reproducible LL measurements and support the potential of LL as a complementary tool for dosimetry and geochronology.
Gesehen am 04.02.2026